Assessing the presence of the joint commission international accreditation requirements in Western Saudi Arabia hospital pharmacies: A cross-sectional study - Ahmed Ibrahim Fathelrahman; Huda Abdullah Almalki; Hanan Rashad Bajunaid; Ghaidaa Khalid Al-Harthi; Manal Omar Aljuaid; Ruqayyah Yahya Majrashi; Mohammed Abdullah Alsuwat (Wolters Kluwer Medknow Publications, 2023)
Objective: The Central Board of Accreditation for Healthcare Institutions (CBAHI) the national Saudi accreditation body accredited most hospitals in Saudi Arabia whereas, the Joint Commission International (JCI) a well-known international accreditation body accredited some hospitals. We assessed Western Saudi Arabia hospital pharmacists' knowledge, opinions, and observations about pharmacy-related JCI accreditation criteria needed for hospitals. Methods: This was a cross-sectional survey-based study conducted among pharmacy personnel working in the Ministry of Health (MOH), Military, and private hospitals in the Makkah region in western Saudi Arabia. The present report represents the findings of descriptive and comparative analyses. Comparative analyses were tested by Student's t-test, analysis of variance, and Chi-square when applicable and a P ≤ 0.05 was considered statistically significant. Findings: One hundred and one pharmacists completed the survey; most of them were from Taif (53.5%) and Jeddah (37.6%) and fewer from Makkah (8.9%). The highest proportions were from MOH (55.4%), private (29.7%), and some from military (14.9%) hospitals. They worked mostly in hospitals accredited with CBAHI (93.1%) than JCI (58.4%) and only (41.6%) worked with quality units. Correct answers on knowledge items ranged from 14.9% to 65.3%. On five-point Likert Scale, they showed supportive ratings on how they perceived the importance of JCI statement provided (overall average score: 3.78) and on how statement criteria are implemented in their hospitals (overall average score: 3.76). Higher proportions of those working in quality units compared to their counterparts were aware that accreditation cycles for JCI and CBAHI are identical (66.7% vs. 55.9%, P = 0.009) and that JCI criteria are more concise than CBAHI (59.5% vs. 52.5%, P = 0.007). Higher proportions of those working in JCI-accredited hospitals compared to their counterparts were aware that JCI criteria are clearer than CBAHI (55.9% vs. 33.3%, P = 0.021) and that JCI criteria are more concise than CBAHI (61% vs. 47.6%, P = 0.012). Conclusion: To a high extent, pharmacists were supportive of JCI criteria and considered the criteria to be implemented in their hospitals. There is a room for improvement to enhance awareness and support of JCI quality criteria among pharmacists.